Portrait of a decade; the second American revolution - Lewis, Anthony, 1927-2013. (New York, Random House, 1964)
This book is a compilation of articles from the New York Times, the work of journalists who have filed millions of words about civil rights during the past ten years.
The revolutionary decade -- The school segregation cases -- The South reacts -- Little Rock -- Montgomery, cradle of the new Negro -- Non-violent direct action -- The role of the federal government -- The right to vote -- Two cities: New Orleans and Atlanta -- Alabama: 1960-1963 -- Mississippi -- The North -- The law.
Includes bibliographical references and index.
Keywords: African Americans -- Civil rights